The Influence of Job Insecurity and Job Satisfaction on Turnover Intention Among Employees at PT Pelayaran Baharimas Kalimantan - Mita Puspita; Devi Yasmin (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to analyze the influence of Job Insecurity and Job Satisfaction on Turnover Intention among employees at PT Pelayaran Baharimas Kalimantan. A quantitative associative approach was used in this research, with a sample of 87 respondents selected through total sampling technique. The instrument testing involved validity and reliability tests, while the classical assumption tests included normality, linearity, and multicollinearity tests. Hypothesis testing was conducted using multiple linear regression, correlation coefficient (R), coefficient of determination (R²), simultaneous tests, and partial tests. The results of the multiple linear regression analysis yielded the equation Y = 1.918 + 0.467 X₁ + 0.121 X₂. The correlation coefficient of 0.517 indicates a moderate correlation between Job Insecurity and Job Satisfaction with Turnover Intention. The coefficient of determination (R²) of 0.267 indicates that 26.7% of the variability in Turnover Intention is influenced by the two variables, while the remaining 73.3% is influenced by other factors not examined in this study. The simultaneous test showed an F value of 15.299, which is greater than the F table value of 3.10, indicating a significant simultaneous effect of Job Insecurity and Job Satisfaction on Turnover Intention. The partial tests revealed that Job Insecurity (p-value = 0.000) and Job Satisfaction (p-value = 0.044) both significantly influence Turnover Intention, with p-values less than 0.05 for both variables. This study provides empirical evidence that both Job Insecurity and Job Satisfaction significantly affect Turnover Intention, which can be considered by management in managing human resources within the company.